A light in the dark: DNA barcoding provides new data about the taxonomy of the Italian Luciola (Coleoptera, Lampyridae) fireflies - Mori, Emiliano; Viviano, Andrea; Baratti, Mariella; Serafini, Elisa; Gabbrielli, Bianca; Picchi, Malayka Samantha; Giannetti, Daniele; Mascalchi, Cristina; Ancillotto, Leonardo (Zootaxa, 2025)
Environmental pollution and agricultural intensification are threatening insects worldwide, and reliable taxonomy is pivotal to protect these taxa, particularly endemic species. Despite their wide distribution, lampyrid beetles (Lampyridae)—well-known as fireflies—are poorly studied in terms of taxonomy, particularly in Europe. Accordingly, as for almost all insects, the description of most species is only based on a few morphological featuresSince genetic analyses can provide valuable support in taxonomic studies, in this work, we investigated the species identity of an Italian endemic firefly, Luciola pedemontana (Curtis, 1843), with respect to other congeneric species, namely Luciola italica (Linnaeus, 1767) and Luciola lusitanica (Charpentier, 1825) by applying Barcoding technique. Particularly, L. pedemontana has been for long considered as a synonym of L. lusitanica or as a subspecies of L. italica. Italy hosts the highest diversity of firefly species in Europe, but the Luciola inter-specific phylogenetic relationships and species delimitations are still poorly known. With the aim to assist morphological analyses in the taxonomic characterization of species of the genus Luciola in Italy, we sequenced the cytochrome oxidase subunit I gene (COI) fragment of 40 individuals from 18 sites in Central Italy. Our analysis confirmed L. pedemontana as a well-supported monophyletic clade and as the sister taxon of L. italica. Furthermore, a low intraspecific genetic variation was found between L. lusitanica and L. pedemontana and between Luciola unmunsana + Luciola papariensis. Genetic data obtained for the Luciola species can help to improve conservation measures for L. pedemontana, strongly required to protect this Italian endemic taxon, which is currently threatened by light pollution and environmental alterations.